2021
DOI: 10.1016/j.jsb.2020.107690
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights of key enzymes into therapeutic intervention against SARS-CoV-2

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…Proline-type derivatives (1-3) moderately inhibited M pro , but their inhibitory activities were obviously weaker than those of the malonic acid-type derivatives. Fullerenol (5) showed no inhibitory activity against M pro at 1.0 mM, indicating that a number of hydroxy groups attached to the fullerene surface lost the inhibitory activity. Compound 4, which has a hydroxymethylcarbonyl moiety, is a transition-state mimic isostere of HIV protease substrate processing and showed potent e cacy against HIV protease in our previous report, [12] and it exhibited weak inhibition against M pro .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proline-type derivatives (1-3) moderately inhibited M pro , but their inhibitory activities were obviously weaker than those of the malonic acid-type derivatives. Fullerenol (5) showed no inhibitory activity against M pro at 1.0 mM, indicating that a number of hydroxy groups attached to the fullerene surface lost the inhibitory activity. Compound 4, which has a hydroxymethylcarbonyl moiety, is a transition-state mimic isostere of HIV protease substrate processing and showed potent e cacy against HIV protease in our previous report, [12] and it exhibited weak inhibition against M pro .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 16 nonstructural proteins, nsp3 (papain-like protease, PL pro ), nsp5 (main protease, M pro , or 3-chymotrypsin-like protease, 3CL pro ), nsp12 (RNA-dependent RNA polymerase), nsp13 (helicase), nsp14 (N7-methyltransferase), and nsp16 (2'-O-methyltransferase) act as enzymes. [5] Thus, while there are many potential targets for COVID-19, SARS-CoV-2 M pro plays an important role in the cleavage of viral polyproteins into functional proteins and is recognized as an attractive target for antiviral drugs. SARS-CoV-2 M pro is a cysteine protease with a catalytic dyad comprised of Cys145 and His41.…”
Section: Introductionmentioning
confidence: 99%
“…Four key enzymes of SARS-COV-2, such as RdRp, 3CLp, papain-like protease, helicase, and ACE-2; and transmembrane serine protease (Host factors), play an essential role in disease establishment. Interestingly, α-glucosidase in the endoplasmic reticulum is a promising target for exploring anti-SARS-CoV-2 medicines 23 .…”
Section: Coronavirus Classification and Mechanism Of Cell Entrymentioning
confidence: 99%
“…The 3-Chymotrypsin-like protease (3CL pro ) is a cysteine protease that facilitates the proteolytic processing of the viral polyproteins to yield functional proteins essential for the packaging of new virions [ 6 ]. It is one of the most important components of viral replication as it cleaves the replicase polyprotein after its translation at 11 different sites releasing most of the functional protein components of the replicase-transcriptase complex, hence it is also known as main protease (M pro ) of coronaviruses [ 7 ]. Amino acid sequence alignments of this protease revealed that, SARS-CoV-2 3CL pro had ∼96% sequence identity with the previous SARS-CoV 3CL pro , and ∼50% sequence identity with MERS-CoV 3CL pro [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its substrate specificity is primarily defined by the residues at the P1, P1′ and P2 positions of the peptide substrate. These positions are highly conserved in all coronaviruses in particular the presence of glutamine at the P1 position (N-terminus of the scissile bond) of the substrate is strictly required for 3CL pro binding across all coronaviruses [ 7 ]. Inhibition of 3CL pro by compounds is not expected to interfere with human proteases since the protease has no homologue in human [ 6 ].…”
Section: Introductionmentioning
confidence: 99%